THE EFFECT OF FAMILY CONTACT HISTORY AND SUPPORT ON THE HEPATITIS B IN PREGNANT WOMEN IN SOUTH KONAWE DISTRICT: HEPATITIS B IN PREGNANT WOMEN - Dian Andraini; Timbul Supodo; Sunarsih Sunarsih (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2022)
Background: From the initial data collection, there  were confirmed to be positive for Hepatitis B, including pregnant women and did not check their pregnancies at health care facilities. They preferred to have their pregnancy checked by traditional birth attendants.This was due to several factors including knowledge. Knowledge is something that is known to be related to the learning process, this learning process is influenced by various factors, both from within such as motivation and from outside in the form of available information facilities and socio-cultural conditions. Methods: This type of quantitative research uses a case control study design with a retrospective approach. The population of all pregnant women examined was 6,584 people. The sample is 70 people with sampling using the Lameshow formula. Results: The chi square test value of contact history is 24,107 which is greater than X2 table = 3.841 and p value = 0.000 and and family support is 12.338 which is greater than X2 table = 3.841 and p value = 0.000. Conclusion: There is an effect between contact history and family support with the incidence of Hepatitis B in pregnant women in South Konawedistric.